Gambaran radiologi lesi litik pada manus: serial kasus - Jessica Harlan; Elysanti Dwi Martadiani; Made Widhi Asih; I Wayan Juli Sumadi (Intisari Sains Medis, 2021)
Background: Lytic lesion of the hand has been challenging in making the differential diagnoses. Tumor and tumor-like lesions present with a wide spectrum of radiological changes.Cases: The first patient is a 17 years old male presents with a painless lump in the left 5th finger, suggested as benign bone tumor. The second patient is a 28 years old male presents with a painful lump in the left 3rd finger,suggested as close fracture of the left metacarpal of the hand. The third patient is a 11 years old male presents with a painless lump and open wound in the right 2nd finger,suggested as aggressive bone tumor. First patient‘s hand radiographs reveal expansile lytic lesions with narrow transitional zone, endosteal scaloping, ring and arc calcification, no perisoteal reaction, no cortical destruction in metadiaphysis of 5th metacarpal and proximal phalanx of the left hand, suggested as primary benign bone tumor, suggested enchondroma. Histomorphology result suggested as enchondromatosis. Second patient‘s hand radiographs reveal expansile lytic lesion with narrow transitional zone and cortical destruction, no periosteal reaction, no calcification in epiphysis to diaphysis of 3rd proximal phalanx of the left hand, suggested as primary benign bone tumor, suggested giant cell tumor. Histomorphology result suggested as benign giant cell tumors of the bone. Third patient’s hand radiographs reveal fusiform expansile lytic lesion with narrow transitional zone causes enlargement of diaphysis with cortical destruction and soft tissue mass, no periosteal reaction, no calcification in 2nd proximal phalanx of right hand, suggested as tuberculous dactylitis, suggested non tuberculous osteomyelitis. Histomorphology result suggested as tuberculous process.Conclusion: Imaging and histomorphology play an important role in differentiating tumor and tumor-like lesions in bone. Recognition of imaging appearance of these lesions may help clinicians make a decision for the treatment. Latar Belakang: Lesi osteolitik pada manus menjadi tantangan dalam membuat diagnosis banding. Tumor dan lesi yang menyerupai memiliki gambaran radiologi beragam.Kasus: Pasien pertama laki-laki usia 17 tahun dengan keluhan benjolan yang tidak nyeri pada jari ke 5 tangan kiri dengan kecurigaan tumor tulang jinak. Pasien kedua laki-laki usia 28 tahun dengan keluhan benjolan yang nyeri pada jari ke 3 tangan kiri dengan kecurigaan fraktur tertutup pada metacarpal tangan kiri. Pasien ketiga laki-laki usia 11 tahun dengan keluhan benjolan disertai luka terbuka pada jari ke 2 tangan kanan dengan kecurigaan tumor tulang agresif. Radiografi manus pasien pertama mengesankan lesi litik ekspansil dengan narrow transitional zone pada metadiafisis metacarpal digiti V dan phalang proksimal digiti V manus kiri dengan endosteal scalopping, tidak tampak reaksi perisoteal maupun destruksi korteks, matriks kalsifikasi ring and arc yang mengesankan tumor tulang primer jinak, mengesankan enchondroma. Histomorfologi sesuai gambaran enchondromatosis. Radiografi manus pasien kedua mengesankan lesi litik ekspansil dengan narrow transitional zone yang menyebabkan destruksi korteks pada epifisis hingga diafisis phalang proksimal digiti III manus kiri dengan keterlibatan jaringan lunak, tidak tampak matriks kalsifikasi maupun reaksi periosteal yang mengesankan gambaran giant cell tumor. Histomorfologi sesuai gambaran giant cell tumor tulang jinak. Radiografi manus pasien ketiga mengesankan lesi litik ekspansil fusiform dengan narrow trazitional zone yang menyebabkan pelebaran diafisis dengan destruksi korteks dan keterlibatan jaringan lunak pada phalang proksimal digiti II manus  kanan, tidak tampak matriks kalsifikasi maupun reaksi periosteal yang mengesankan suatu daktilitis tuberkulosis dengan diagnosis banding osteomyelitis non tuberkulosis. Histomorfologi sesuai gambaran tuberculosis. Simpulan: Pencitraan dan histomorfologi memainkan peran penting dalam membedakan tumor dan lesi yang menyerupai tumor pada tulang. Mengenali lesi ini sangat penting karena membantu klinisi untuk menentukan terapi.